The part-time worker and his protection in the Colombian legal framework - Cortina Candanoza, Lizeth; Díaz Velandia, Carlos; Mendoza Torres, Gabriel Andrés (DIXI, 2022)
A working day of less than thirty days, affiliation to the health system and a salary lower than the legal minimum monthly salary in force are the characteristics of a part-time worker. This figure has taken great relevance in the current labor environment in Colombia, which is why this research determines the legal development in relation to it. The legislative progress is described and the pronouncements in Colombian jurisprudence are identified by means of a legal analysis. An exploratory methodology is used, the purpose of which is to highlight fundamental aspects of the subject and to use a qualitative-descriptive model.